1972
DOI: 10.1111/j.1365-2362.1972.tb00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Mono‐ and Divalent Electrolyte Patterns, pCO2 and pH in Relation to Flow Rate in Normal Human Parotid Saliva*

Abstract: In parotid saliva of normal subjects the pH, pCO2 and concentrations of sodium, potassium, calcium, magnesium, bicarbonate and inorganic phosphate were determined continuously after stimulation of salivary secretion by pilocarpine. The electrolyte concentrations showed a marked dependence on salivary flow rate. Sodium, calcium and bicarbonate concentrations and pH increased with increasing flow rate but the concentrations of potassium, magnesium and inorganic phosphate decreased with increasing flow rate. In g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
1
1

Year Published

1973
1973
2010
2010

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 26 publications
4
19
1
1
Order By: Relevance
“…This is also in contrast with the results presented here. The present study confirms the finding of Kreusser et al [1972] showing a pH in crease with flow rate. Since the ionized cal cium concentration decreases slightly with increasing salivary pH value [Lagerlof, 1980], a decrease in the ratio ionized cal cium/total calcium could be expected and was subsequently found in our study.…”
Section: Discussionsupporting
confidence: 81%
“…This is also in contrast with the results presented here. The present study confirms the finding of Kreusser et al [1972] showing a pH in crease with flow rate. Since the ionized cal cium concentration decreases slightly with increasing salivary pH value [Lagerlof, 1980], a decrease in the ratio ionized cal cium/total calcium could be expected and was subsequently found in our study.…”
Section: Discussionsupporting
confidence: 81%
“…It is well known that the protein concentration increases at most twofold as parotid flow increases from the resting state to 1 ml/min (6). In contrast, sodium levels can increase over 30-fold, from a resting 2 to 60 meq/liter or more (6,14). The increase in sodium levels in stimulated secretion is due to the reduced reabsorption of this ion in the ductal system under these conditions.…”
Section: Fig 4 Candidacidal Activities Of Undialyzed Parotid Secretmentioning
confidence: 94%
“…With respect to phosphate concentration, the group presenting the highest rate was that of patients with SSs. However, we note that the levels increase in SSp, which is discordant since it has been shown that phosphate concentration varies inversely with salivary flow rate (16,17). In all groups, differences were statistically significant in relation to controls.…”
Section: Discussionmentioning
confidence: 57%